Dari Digitalisasi Akuntansi ke Pembukuan Digital: Strategi Tingkatkan Daya Saing Entitas Bisnis Kecil - Sitti Nur Syafika; Masyhuri Masyhuri (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the transition from conventional accounting to simple digital bookkeeping as a strategy to enhance the competitiveness of small business entities in the digital economy era. The study employs a qualitative approach based on a literature review, examining various scientific articles, academic books, and relevant publications on accounting digitization, MSME financial management, and digital business transformation. The analysis is conducted using a descriptive-interpretive method through data reduction, literature classification, conceptual synthesis, and critical interpretation of various findings from previous studies. The results indicate that simple digital bookkeeping is more suitable for SMEs than complex formal accounting systems because it enhances recording efficiency, accelerates access to financial information, strengthens business transparency, and supports real-time data-driven decision-making. The implementation of digital bookkeeping also contributes to improved financial discipline, control of operational costs, and access to formal financing. The effectiveness of the system’s implementation is influenced by digital literacy, the simplicity of the application, guidance, and integration with the business strategies of small enterprises.